Advances in Modeling Alzheimer's Disease In Vitro. Issue 12 (28th October 2021) - Sharma, Navatha Shree; Karan, Anik; Lee, Donghee; Yan, Zheng; Xie, Jingwei
Abstract : Alzheimer's disease (AD) is the most common neurodegenerative disease characterized by progressive memory loss and cognitive impairment, thereby disrupting the performance of daily activities. Numerous therapeutics have shown efficacy in animal AD models but failed in human patients. The key to understanding the etiology of AD lies in the development of effective disease models, which can ideally recapitulate all characteristics of the disease. Over the years, different approaches including in vitro, in vivo, and in silico models are able to resemble certain features of AD. In this review, the significance of different in vitro models including their merits and limitations in modeling AD is discussed, which will give a better perspective on the development of a comprehensive model that can mimic human AD. This starts with a brief introduction to AD and its pathology. Then it mainly focuses on the two‐dimensional, three‐dimensional and microfluidic in vitro models of AD that have made significant advancements in understanding AD pathology and aiding in screening effective therapeutics. Several 3D neural tissue engineering models developed in the last two decades along with a discussion on the future prospects in the development of efficient in vitro AD models are further highlighted. Abstract : This work reviews the 2D, 3D, and microfluidic in vitro models of AD that have made significant advancements in not only understanding AD pathology but also aiding in screening effective therapeutics.